Experienced Loneliness in Home-Based Rehabilitation: Perspectives of Older Adults With Disabilities and Their Health Care Professionals. (February 2019) - Lykke, Sine; Handberg, Charlotte
This study aimed to describe and interpret perspectives of older adults with disabilities and their health care professionals (HCPs) on experienced loneliness during home-based rehabilitation. The interpretive description methodology guided the study. Data included semistructured individual interviews with seven older adults and a focus group interview with three HCPs. The analysis revealed four main findings that symbolized experienced loneliness. "Unspoken pain" and "gatekeeping emotions" concerning experienced loneliness as a taboo and stigma during rehabilitation were closely connected. "Resignation" and "awaiting company" signified the consequences of experienced loneliness when not addressed. Unspoken pain, gatekeeping emotions, resignation, and awaiting company were dominating experiences in the lives of the older adults during a home-based rehabilitation program following disability. This had restrained them from verbalizing and coping with loneliness during rehabilitation and life in general. The HCPs' attempt to provide support for the older adults in coping with loneliness appeared to be characterized by gatekeeping emotions and keeping hidden agendas.